2020
DOI: 10.3390/en13215611
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Based Order Reduction of a Chemical Membrane Degradation Model for Low-Temperature Proton Exchange Membrane Fuel Cells

Abstract: The chemical degradation of the perfluorinated sulfonic acid (PFSA) ion-exchange membrane as a result of an attack from a radical species, originating as a by-product of the oxygen reduction reaction, represents a significant limiting factor in a wider adoption of low-temperature proton exchange membrane fuel cells (LT-PEMFCs). The efficient mathematical modeling of these processes is therefore a crucial step in the further development of proton exchange membrane fuel cells. Starting with an extensive kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The undesired oxidation, decreasing the active sites for reduction of oxygen at the cathode, and carbon monoxide poisoning of the cathode catalyst are other methanol crossover challenges [142][143][144][145]. Nafion, as the most common PEM used in DMFCs, suf-fers from the methanol crossover despite its supreme proton conductivity and outstanding chemical, thermal, and mechanical stability [146][147][148]. One attempt to decrease the methanol crossover in Nafion is to use 2D h-BN as reinforcement.…”
Section: Fuel Cells 241 Membranementioning
confidence: 99%
“…The undesired oxidation, decreasing the active sites for reduction of oxygen at the cathode, and carbon monoxide poisoning of the cathode catalyst are other methanol crossover challenges [142][143][144][145]. Nafion, as the most common PEM used in DMFCs, suf-fers from the methanol crossover despite its supreme proton conductivity and outstanding chemical, thermal, and mechanical stability [146][147][148]. One attempt to decrease the methanol crossover in Nafion is to use 2D h-BN as reinforcement.…”
Section: Fuel Cells 241 Membranementioning
confidence: 99%
“…It has been reported that Ce 3+ and Mn 2+ or these oxide nanoparticles, whose cations can undergo fast reversible redox reactions and quench radicals by donating or accepting electrons under aqueous conditions, are very effective at protecting PEMs from chemical degradation, and hence, PEM stabilization has been achieved by incorporation of radical scavenger species by a variety of methods. The presence of Ce 3+ scavengers leads to a 20-fold reduction in the MEA degradation rate and a nearly 1000-fold reduction in fluoride reduction. Compared with Ce 3+ mitigation, equivalent levels of Mn 2+ doping are 5–10 times less effective .…”
Section: Introductionmentioning
confidence: 99%
“…There are many publications that include this pair of reactions in the proposed mechanism, assigning second-order kinetics to both steps. 19,30,31,60,[69][70][71][72][73][74][75][76][77][81][82][83][86][87][88][89]91,92,94,96,[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154] The H + in the second step is bracketed to indicate that it is required for the stoichiometry but does not appear in the rate law. This reaction pair corresponds to a reversible equilibrium, but it violates the principle of detailed balancing because the rate expressions in the forward and reverse directions are second order, which disagrees with the form of the equilibrium expression.…”
Section: Improper Reversible Stepsmentioning
confidence: 99%